STUDIES ON THE ROOT ANATOMY OF RUBBER PRODUCING ENDEMIC OF KAZAKHSTAN, TARAXACUM KOK-SAGHYZ L.E. RODIN - . B. khmetova; N. M. Mukhitdinov; A. Ydyrys; A. A. metov; Z. A. Inelova; M. Öztürk (Journal of Animal and Plant Sciences, 2018)
This paper highlights morpho-metric and anatomical characteristics of a rare, endangered, endemic species Taraxacum kok-saghyz from Kazakhstan. The plant has been investigated using three different populations during young generative stages. The morphometric features recorded here from the natural populations show that, height of T. kok-saghyz plants and diameter of crown significantly increase in generative period. Plant roots contain milky tubes filled with coagulated latex - rubber threads, and are characterized by varying degrees of specific tissue development, depending on place of growth. Thus, it was found that plants of population 2 are characterized by significant development of primary cork ( 553.12 mkm=micron) and diameter of central cylinder ( 432.70 µ), in which narrow clearance xylem elements are concentrated. On the contrary, plants of population 3, have all signs of body xeromorphic structures (strong development of cover tissue and presence of more wide clearance vessels of water conducting tissue). Dark chestnut mountain soil type is the most favorable for plant growth and development. This taxon is a hygrophilous plant therefore water supply conditions affect distinctive features of plant internal structure. However, from 1950 onwards the imports of natural
Keywords: Taraxacum kok-saghyz; Anatomy; Rare/endemic species; Kazakhstan.